Chemotactic Control of the Two Flagellar Systems of Rhodobacter sphaeroides Is Mediated by Different Sets of CheY and FliM Proteins - del Campo, Ana Martínez (American Society for Microbiology (ASM), 2007)
Rhodobacter sphaeroides expresses two different flagellar systems, a subpolar flagellum (fla1) and multiple polar flagella (fla2). These structures are encoded by different sets of flagellar genes. The chemotactic control of the subpolar flagellum (fla1) is mediated by three of the six different CheY proteins (CheY6, CheY4, or CheY3). We show evidence that CheY1, CheY2, and CheY5 control the chemotactic behavior mediated by fla2 flagella and that RSP6099 encodes the fla2 FliM protein.